CHANGING AWARENESS, TESTING AND TRANSMISSION OF HIV IN PREGNANCY - Dr. Ruma Sarkar; Dr. Shoadashi Saxena; Dr. Ranjana Sarkar; Dr. Rachana Bhatnagar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
INTRODUCTION: Human immunodeficiency virus (HIV) infection is a global health concern, with sexual transmission being predominant in India, accounting for 86% of cases. Despite a decline in HIV incidence, the prevalence remains significant, affecting approximately 2.3 million people in India. Henceforth, this study aimed to assess changes in the level of testing and mother-to-child transmission (MTCT).METHODOLOGY: A retrospective descriptive study was conducted at the Prevention of Mother-to-Child Transmission (PMTCT) centre, analyzing records of patients from January 2012 to December 2013 and January 2021 to December 2022. Data included testing, sociodemographic factors, and pregnancy outcomes.RESULTS: In 2012-2013, 11,232 patients were tested, with a 0.5% prevalence among antenatal patients. The recent period of 2021-2022 saw increased testing (20,767), with a decreased prevalence of 0.3%. Notably, the MTCT rate dropped to 3%. Analysis of age, parity, literacy, and residential distribution revealed changing trends. Migrant labourers remained predominant, and antenatal outcomes showed a shift over time.CONCLUSION: Seropositivity among antenatal populations poses a significant challenge. While national programs show progress, there is a need to address complexities in HIV seropositivity. Bridging gaps in reproductive health and targeted interventions are imperative.